Spiritual Legacy, Sufi Identity, and Mystical Knowledge in Taṣliya formulae - Sajid, Mehdi (Die Welt des Islams, 2023)
The tradition of taṣliya texts and practices in Sufism constitute an important source of Muslim intellectual and religious history. Previous studies have argued that these texts were more than mere cultural expressions of devotion to Prophet Muḥammad. Following this line of thought, this article seeks to deepen our grasp of the significance of taṣliya formulae in Sufi contexts. Emphasis will be placed on their role in popularizing various mystical-philosophical teachings and prophetical doctrines that shaped Muslims’ imaginations of the Prophet throughout the centuries.